Rehabilitating probation: experiences and impacts of unification among managers and practitioners in a probation service region, 2022-2024 - Millings, Matthew (UK Data Service, 2025)
Rehabilitating Probation: Rebuilding culture, identity and legitimacy in a reformed public service was a three-year (2022-2025) ESRC funded research project that examined the implementation, experiences and consequences of a significant and unprecedented programme of public service reform that brought formerly outsourced probation services back into the public sector. Probation services across England and Wales were reunified following a period of large-scale privatisation under Transforming Rehabilitation reforms implemented in 2014, which had led to the establishment of a publicly operated National Probation Service (NPS) and a number of private Community Rehabilitation Companies (CRCs). In June 2021 the public and private arms of probation were brought back together under a newly constituted public Probation Service. The Rehabilitating Probation research project captured the experiences and consequences of reform at local, regional and national levels and from a variety of perspectives, including: probation staff; senior managers; policy makers; service users; and external stakeholders. The research explored the impact of reform on the roles, identities and cultures of probation workers and narrated how a newly reconfigured probation service sought to (re-)build legitimacy with its external partners. Rehabilitating Probation: Rebuilding culture, identity and legitimacy in a reformed public service was a three-year (2022-2025) ESRC funded research project that examined the implementation, experiences and consequences of a significant and unprecedented programme of public service reform that brought formerly outsourced probation services back into the public sector. As a key component of the criminal justice system, the Probation Service is responsible for protecting the public, managing risk, and supporting the rehabilitation of offenders. It supervises approximately 240,000 individuals serving community-based sentences or released on licence following imprisonment. Probation services across England and Wales were reunified following a period of large-scale privatisation under Transforming Rehabilitation reforms implemented in 2014, which had led to the establishment of a publicly operated National Probation Service (NPS) and a number of private Community Rehabilitation Companies (CRCs). In June 2021 the public and private arms of probation were brought back together under a newly constituted public Probation Service. The second major programme of structural reform in probation services in a decade had far-reaching implications - not only for how probation work is delivered, but also for understanding how public services respond when outsourcing policies fail. It provided a unique opportunity to explore how individual and organisational identities are reconstructed following significant organisational change, and how institutions work to (re)build the confidence of their staff, as well as that of key partners and stakeholders such as the courts and police. The Rehabilitating Probation research project captured the experiences and consequences of reform at local, regional and national levels and from a variety of perspectives, including: probation staff; senior managers; policy makers; service users; and external stakeholders. The research explored the impact of reform on the roles, identities and cultures of probation workers and narrated how a newly reconfigured probation service sought to (re-)build legitimacy with its external partners. The research project comprised five interconnected work packages (WPs), each offering a distinct perspective on the structural reform of probation services. In WP1, the team conducted 191 interviews with probation staff and managers within a single case study region, capturing detailed, longitudinal insights into how individuals experienced the reform over time. WP2 extended this lens nationally, with 38 interviews conducted across three annual sweeps with Regional Probation Directors from all 12 Probation Service regions, enabling a broader understanding of the reform process and validating the case study’s representativeness. WP3 focused on external perceptions, involving 70 interviews with national and local criminal justice partners and stakeholders - such as Police and Crime Commissioners, members of the Judiciary, HM Courts and Tribunal Service, Police leaders and officers and Prison Governors - to explore how the unified service positioned itself and was perceived by key collaborators. WP4 examined the policy dimension, with 40 interviews conducted in three sweeps with senior policy officials to trace the evolving thinking and implementation strategies at the national level. Finally, WP5 adopted a participatory approach, using co-designed exercises and workshops led by peer researchers to bring together individuals with diverse experiences of probation. These sessions explored foundational questions about the purpose and future direction of probation, grounding the research in lived experience and collaborative inquiry.